ገበታ: የአየር ለውጥን መቋቋም ስለሚችሉ የተሻሻሉ የእንስሳት መኖ ቴክኖሎጂዎች የራዲዮ ፕሮግራም፡ ክፍል አራት - International Livestock Research Institute (International Livestock Research Institute, 2022)
Episode four, which aired on Debre Birhan Fana FM 94.0 on 12 July 2022, focuses on fodder beet, a well-adapted forage species in Ethiopian highlands. Farmers in Angolela Kebele of Basona Worena District, in the North Shewa Zone, shared their experiences of planting fodder beet and its benefits. Melkamu Bezabih, livestock feed and forage scientist at ILRI, also explained about fodder beet management. This radio program series is produced by Africa RISING and AICCRA as part of the partnership – Use of interactive radio to scale-up feed and forage innovation technologies in Ethiopia.